CLASS STRUGGLE IN SPARTACUS MOVIE DIRECTED BY ROBERT DORNHELM: A MARXIST APPROACH - MARVIANINGRUM , ANESYA (2009)

(untitled)
The major problem of this study is to elucidate the struggle of Spartacus reflected in Robert Dornhelm’s Spartacus movie. The objectives of the study are; to analyse the structural elements of the movie and to analyse the character of Spartacus based on Marxist perspective.